Study the Effect of Preparation and Diagnosis of Polyethylene Terephthalate (PET) As Additive Modification on Concrete Properties - Bachari, Thamir Salman (Basrah Journal for Engineering Sciences, 2015)
The polyethylene terephthalate (PET) was prepared from PET flakes of empty local water drinking bottles and diagnosis by infrared spectroscopy (IR). The glass transition temperature, melting temperature T m and heat capacity were indicated by differential scanning calorimeter (DSC). Part hundred ratios (phr , s) of (PET) were added to study its effect on concrete properties. Additives of (phr) impart performance such as increased cement dispersion, enabling drastically reduced water requirements. Enhance the mortar cubes performance; depend on the compatibility of cement with PET. Porosity of mortar cubes with cement, sand and added PET products were calculated. Maximum and minimum Compressive strength were calculated 58.76 MPa, and 24.0 MPa at phr 0.04 and 0.07 of PET with cement. And PET with cement and sand were calculated 16.5 MPa and 4 MPa at dosages 0.03 gm. and 0.08 gm. The relative dosages in calculating porosity percentages are (0.06, 0.1 and 0.3) gm.